Improving Environmental Performance of the Muslim World: Evidence from Affluent Countries - Ismail, Roslina; Saputra, Jumadil; Aziz, Azlina Abdul (International Journal of Energy Economics and Policy, 2019)
Both the Muslim and non-Muslim worlds have a shared commitment to mitigate environmental degradation and repair already degraded areas. However, not much has been said about the good environmental performance of the affluent states of the Muslim world. This study uses the Environmental Performance Index (EPI) produced by the University of Yale to analyse how to design better strategies for the upper-middle income (UMIE) and high-income Muslim countries (HIE) when dealing with their environmental performance. This study proposes that the choice of strategy should depend on the environmental and political economy of the countries, the status and ranking of their environmental performance, and an openness to learning from the successes of the environmental foreign policy successes of other affluent Muslim countries. Keywords: Environmental performance, Environmental degradation, Environmental foreign policy, Energy JEL Classifications: O13, Q, Q56 DOI: https://doi.org/10.32479/ijeep.7788